Valorization of fruit and vegetable processing by-products/wastes - Ozkan, Gulay; Günal-Köroğlu, Deniz; Capanoglu, Esra (Elsevier BV, 2023)
Fruit and vegetable processing by-products and wastes are of great importance due to their high production volumes and their composition containing different functional compounds. Particularly, apple, grape, citrus, and tomato pomaces, potato peel, olive mill wastewater, olive pomace and olive leaves are the main by-products that are produced during processing. Besides conventional techniques, ultrasound-assisted extraction, microwave-assisted extraction, pressurized liquid extraction (sub-critical water extraction), supercritical fluid extraction, enzyme-assisted extraction, and fermentation are emerging tools for the recovery of target compounds. On the other hand, in the view of valorization, it is possible to use them in active packaging applications, as a source of bioactive compound (oil, phenolics, carotenoids), as functional ingredients and as biofertilizer and biogas sources. This chapter explains the production of fruit and vegetable processing by-products/wastes. Moreover, the valorization of functional compounds recovered from the fruit and vegetable by-products and wastes is evaluated in detail by emphasizing the type of the by-products/wastes, functional compounds obtained from these by-products/wastes, their extraction conditions and application areas.
Keywords: Phenols; Fruit; Vegetables; Carotenoids